Sociodemographic and clinical profile of hemodialysis users in the south of Rio Grande do Sul, Brazil. - De Paula, Elaine Amaral (2022)
Aim: to characterize the sociodemographic and clinical profile of people undergoing hemodialysis in the south of Rio Grande do Sul, Brazil. Methods: This was a descriptive, quantitative, and cross-sectional study carried out with the application of a structured questionnaire and the review of the medical records of 335 adults undergoing hemodialysis from seven hemodialysis clinics distributed in five municipalities in Rio Grande do Sul from March 2016 to March 2017. The researchers evaluated the sociodemographic data, family history, lifestyle, etiology of the disease, and comorbidities; descriptive statistics were used for the analysis. Results: Of the 335 adults undergoing hemodialysis, 59% were men, 47% elderly, and 59% with low family income. Diabetes mellitus was the main etiology of kidney disease (28%); 50% reported an unrestricted diet and 59.8% ingested more than 800 ml of liquids daily, including 10% alcoholic beverages, and 77.0% reported anuria, 42% were previous smokers and 24% reported family history of the disease. In regards to expenses related to the hemodialysis treatment, 80.3% reported some type of expenditure, especially with medicines for 88.4%; the occurrence of infectious diseases, such as hepatitis B, C and HIV was found, respectively, in 3.9%, 7.5 % and 2.1% of the sample. Conclusion: The findings pointed to the need to reorganize the care for chronic kidney disease within the scope of primary and secondary care services; this with the aim of early detection of chronic kidney disease and the clinical control of risk factors, including diabetes, in in less favored socioeconomic groups mainly. This would facilitate the population's access to the services of the healthcare network.